2015
DOI: 10.1002/job.2057
|View full text |Cite
|
Sign up to set email alerts
|

Psychological ownership: A review and research agenda

Abstract: The concept of psychological ownership (PO) reflects a state in which individuals feel as though the target of ownership (e.g., job or organization) is theirs. In recent years, there has been an expansion of research linking PO with a range of desirable employee attitudes and behaviors. However, the theoretical foundations of the construct, its measurement, the factors that influence its development, and when and how it influences outcomes are areas of continued debate in the literature. In this article, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
300
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(347 citation statements)
references
References 93 publications
12
300
2
2
Order By: Relevance
“…Psychological ownership has been receiving increasingly more attention as a core feeling in the experience of work. The findings from a recent narrative review indicate that psychological ownership influences a variety of workplace outcomes (Dawkins, Tian, Newman, & Martin, ). However, there has been a lack of empirical research on how feelings of ownership develop in the workplace, particularly from a job design perspective (with exceptions, e.g., Brown et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological ownership has been receiving increasingly more attention as a core feeling in the experience of work. The findings from a recent narrative review indicate that psychological ownership influences a variety of workplace outcomes (Dawkins, Tian, Newman, & Martin, ). However, there has been a lack of empirical research on how feelings of ownership develop in the workplace, particularly from a job design perspective (with exceptions, e.g., Brown et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Self-identity is also strengthened by feelings of possession, which is an expression of the self and clarifies who someone is (Dawkins, Tian, Newman, & Martin, 2015).…”
Section: A Stewardship Perspective On the Relationship Between Po And Eomentioning
confidence: 99%
“…In addition, studies have been suggested that PO reflects a sense of responsibility and accountability for the ownership target (Avey, Avolio, Crossland, & Chen, 2009;Dawkins et al, 2015). For example, Parker, Wall, and Jackson (1997) suggested that the individual sense of ownership is expressed by concern and perceived responsibility for the object.…”
Section: A Stewardship Perspective On the Relationship Between Po And Eomentioning
confidence: 99%
See 1 more Smart Citation
“…This is because learning from failures requires employees to engage in analytical thinking in order to make the necessary adjustments going forward. However, many employees are reluctant to do so because of lack of ownership and internalization of their job roles (Dawkins et al, 2017). Thus, it is important for managers to help employees internalize and take responsibility of their job roles.…”
Section: Practical Implicationsmentioning
confidence: 99%